Efektifitas Penyelesaian Perkara Melalui E-Court di Pengadilan Agama Jeneponto Perspektif Perbandingan Mazhab - Syah, Ulvi Dwi Juliarti; Lewa, Irfan (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2022)
This thesis research that will be examined by the author is the Effectiveness of Case Resolution Through E-Court at the Jeneponto Religious Court (Comparative Perspective of Schools). This study aims to describe the process and settlement of cases through e-Court at the Jeneponto Religious Court. The type of research used by the researcher is research with qualitative methods, as well as the research location used at the Jeneponto Religious Court and the focus of the research is the effectiveness of case settlement through e-Court at the Jeneponto Religious Court. In this study, the researcher used the purposive sampling method to determine informants. The data collection techniques used were observation, in-depth interviews with several informants, both judges and staff at the Jeneponto Religious Court, and documentation. As well as the data analysis technique used in this study using interactive methods, namely by reducing data, presenting data and or drawing conclusions. The results of this study indicate that the case settlement system through e-Court at the Jeneponto Religious Court is actually present to eliminate unwanted matters in court proceedings, in fact e-court aims to create simple, fast and low-cost principles in the entire litigation process and avoid there are risks such as illegal fees, there are many doors in the legal process, this can be assessed and evaluated by all judicial bodies in Indonesia. The procedure for using e-Courts has been explained in PERMA Number 1 of 2019 in chapter five (5) regarding electronic trials starting from article 19 to article 28. Electronic trials require the trial process to be carried out more simply, quickly and at low cost.